2019
DOI: 10.3389/fphys.2019.00526
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Aspects of Muscle Specialization Demonstrate Genotype – Phenotype Interaction Effects in Athletes

Abstract: Introduction Gene polymorphisms are associated with athletic phenotypes relying on maximal or continued power production and affect the specialization of skeletal muscle composition with endurance or strength training of untrained subjects. We tested whether prominent polymorphisms in genes for angiotensin converting enzyme (ACE), tenascin-C (TNC), and actinin-3 (ACTN3) are associated with the differentiation of cellular hallmarks of muscle metabolism and contraction in high level athletes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 71 publications
(133 reference statements)
2
48
0
2
Order By: Relevance
“…Finally, it is also important to point out that genetic predisposition, in part, can explain some of the observed interindividual differences in fiber type make-up [ 42 , 43 ]. In this regard, the ACTN3 R577X genotype has been associated with muscle fiber type composition, where individuals harboring the RR genotype possess more type IIx fibers compared to those with the XX genotype [ 44 ].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Finally, it is also important to point out that genetic predisposition, in part, can explain some of the observed interindividual differences in fiber type make-up [ 42 , 43 ]. In this regard, the ACTN3 R577X genotype has been associated with muscle fiber type composition, where individuals harboring the RR genotype possess more type IIx fibers compared to those with the XX genotype [ 44 ].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In this regard, two of the studies mentioned above which have observed features of sarcoplasmic hypertrophy have been in well-trained bodybuilders ( Macdougall et al, 1982 ; Meijer et al, 2015 ), and this population generally trains with higher volumes. Conversely, there are features of myofibril packing in power athletes ( Meijer et al, 2015 ; Fluck et al, 2019 ), and this population generally trains with higher loads and lower volumes. The two aforementioned studies from our laboratory also support this model ( Haun et al, 2019b ; Vann et al, 2020a ), and it is notable that a reduction in myofilament packing density via sarcoplasmic hypertrophy may also promote certain training adaptations such as increased muscle fiber shortening velocity ( Metzger and Moss, 1987 ).…”
Section: Broader Implicationsmentioning
confidence: 99%
“…A proper mitochondrial turnover is crucial in muscle adaptation to exercise given that abnormal proteostasis leads to loss of contractile proteins in aged muscles [127,128]. However, despite controlled physical activity, complete muscle restoration is impossible due to unavoidable oxidative deterioration of fast glycolytic fibers and enhanced expression of age-related genes insensitive to exercise benefit [129,130].…”
Section: Exercise-an Anti-aging Strategy That Preserves Mitochondria mentioning
confidence: 99%